Red Blood Cell Transfusions and Iron Therapy for Patients Presenting with Acute Upper Gastrointestinal Bleeding: A Survey of Canadian Gastroenterologists and Hepatologists - Kyle J. Fortinsky; Myriam Martel; Roshan Razik; Gillian Spiegle; Zane R. Gallinger; Samir C. Grover; Katerina Pavenski; Adam V. Weizman; Lukasz Kwapisz; Sangeeta Mehta; Sarah Gray; Alan N. Barkun (Canadian Journal of Gastroenterology and Hepatology)
Introduction. There is limited data evaluating physician transfusion practices in patients with acute upper gastrointestinal bleeding (UGIB). Methods. A web-based survey was sent to 500 gastroenterologists and hepatologists across Canada. The survey included clinical vignettes where physicians were asked to choose transfusion thresholds. Results. The response rate was 41% (N=203). The reported hemoglobin (Hgb) transfusion trigger differed by up to 50 g/L. Transfusions were more liberal in hemodynamically unstable patients compared to stable patients (mean Hgb of 86.7 g/L versus 71.0 g/L; p<0.001). Many clinicians (24%) reported transfusing a hemodynamically unstable patient at a Hgb threshold of 100 g/L and the majority (57%) are transfusing two units of RBCs as initial management. Patients with coronary artery disease (mean Hgb of 84.0 g/L versus 71.0 g/L; p<0.01) or cirrhosis (mean Hgb of 74.4 g/L versus 71.0 g/L; p<0.01) were transfused more liberally than healthy patients. Fewer than 15% would prescribe iron to patients with UGIB who are anemic upon discharge. Conclusions. The transfusion practices of gastroenterologists in the management of UGIB vary widely and more high-quality evidence is needed to help assess the efficacy and safety of selected transfusion thresholds in varying patients presenting with UGIB.